Competition between high-speed rail and airlines: Considering both passenger and cargo. (September 2021) - Cai, Dong-ling; Xiao, Yi-bin; Jiang, Changmin
Abstract: With the global express delivery industry growing rapidly, the service that uses high-speed rail (HSR) passenger trains to carry parcels has been introduced in China, signaling that the competition between HSR and air transport is no longer limited to the passenger sector. In this paper, we build a simple model to study the competition between air and rail in both the passenger market and the cargo market. We consider the transport operators face passengers directly but they rely on a forwarder at the downstream for the cargo service. Three scenarios are investigated: 1) both the passenger and the cargo sectors are only served by air transport; 2) the passenger sector is served by both air transport and HSR while the cargo sector is only served by air transport; and 3) both sectors are served by both transport modes. We find that when airlines use aircraft belly to transport cargo while the belly capacity is limited, it is possible that introducing HSR as a competitor in the passenger sector is social welfare deteriorating. However, social welfare will always be improved if HSR enters not only the passenger sector but also the cargo sector. Highlights: This is the first paper to analytically investigate the impacts of high-speed rail express delivery (HSReD). This is the first paper to examine the competition between air transport and HSR in both passenger and cargo markets. It contributes to the literature of air-HSR interaction. It identifies a potential source of welfare reduction caused by new HSR projects. It provides reasons for the government to support the development of HSRed.